Pendekatan dakwah Majlis Agama Islam Selangor terhadap pemohon pengisytiharan murtad / Suariza@Hidayah Muhammad - Suariza@Hidayah , Muhammad (2018)
The apostasy declaration application has occurred among the converts at the Selangor Islamic Religious Council or MAIS. However, since no special enactment for the apostasy case, the Istitabah program was introduced to restore their faith. Even so, there are applicants who intend to apply for apostasy. Hence, this study was conducted to identify the da'wah approach to the apostate declaration from an Islamic perspective, to analyze the MAIS da'wah approach to the apostate declaration and to ascertain how far the MAIS da'wah approach was adopted by the apostate declaration. To obtain data, the study uses library and field methods through interviews, observations. Semi-structured interviews were conducted against ten apostate declaration applicants. Descriptive analysis is done to make a conclusion on the study's findings. Studies have found that apostasy factors are due to disappointment with household failures, heartbroken and family pressure factors. The MAIS party has taken drastic steps to address this issue. The analysis of MAIS da'wah approach to apostasy declaration applicants, MAIS uses the appropriate da'wah approach and is in line with the Islamic will of the apostate declaration. Through da'wah bills of wisdom and wisdom, good advice and teaching and debate in a good way. However, from ten informants of the apostate declaration, three of them received MAIS da'wah approach and seven applicants rejected this approach.